Innate immunity and coeliac disease - Kelly, Stacey (Trinity College (Dublin, Ireland). Department of Immunology, 2008)
Coeliac disease is a gluten sensitive enteropathy in which well defined gliadin peptides initiate a T cell mediated inflammatory response within the small intestine. This disseminates into destruction of the villous architecture and results in lifelong complications upon continued inclusion of gliadin in the diet. Complete removal of gliadin and its related peptides remains the only form of treatment of coeliac disease. Recent evidence supports a role of gliadin and particular peptides in activation of an innate immune response and that these triggering events may influence the subsequent activation of the adaptive immune response. Intervention therapies targeting these initial triggering events of innate immunity offer an attractive alternative to gliadin exclusion from the diet. Numerous studies aimed at these initial events have provided invaluable information about how the disease is established in individuals with the disease susceptibility genes, despite the fact that 30% of the normal population remain unaffected.
Keywords: Immunology, Ph.D.; Ph.D. Trinity College Dublin